Chemical composition of berry essential oils from Juniperus communis L. (Cupressaceae) growing wild in Republic of Macedonia and assessment of the chemical composition in accordance to European Pharmacopoeia - Gjoshe Stefkov; Svetlana Kulevanova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2012)
Chemical composition of fifteen samples of juniper essential oil was analyzed using GC/FID/MS method. Thirteen samples of berries were collected on different locations in south-western part , two of them in central-north region of Republic of Macedonia. The essential oils were obtained by hydrodistillation in a Clevenger type apparatus using official method of European Pharmacopoeia. GC/MS analysis revealed 74 identified components. The predominant fractions of the oils were monoterpene hydrocarbons representing 39.11- 73.38%. Great variability in the chemical composition and content of some components was observed. The most variable components were α-pinene (15.59-43.19%), β-pinene (1.65%-5.35%), β-myrcene (2.89%-26.50%), sabinene (2.80-11.77%), and limonene (2.90-4.46%). In the fraction of oxidized monoterpenes the most abundant was terpene-4-ol (trace - 6.32%) followed by α-terpineol (0.18-1.63%). In the sesquiterpene fraction predominant components were: germacrene D (2.76-10.22%), β-elemene (1.13-3.40%) and trans-(E)-caryophyllene (1.8%- 4.05%). Twelve samples of Macedonian juniper oils comply with European Pharmacopoeia chemical composition requirements for juniper oil and three samples did not, due to lower amount of α-pinene.